চীংলোনগী ৱারী শীংবুন - Singh, Chirom Rajketan (Cultural Research Centre Manipur, 2010)
This is the third of the three volumes of folk tales collected from diffrent villages of Manipur.
Chinglongi Wari Shingbun vol-III
Keywords: Manipuri; চীংলোনগী ৱারী শীংবুন; Chinglongi Wari Shingbun vol-III; Folk Tales; Manipuri; Manipuri